Under the Purdah: Network of Gender, Class, and Religion in Iqbalunnisa Hussain’s Purdah and Polygamy: The Life in an Indian Muslim Household (1944) - Safeer Hussain (Wah Academia Journal of Social Sciences, 2025)
While the canon of 1940s subcontinental literature is dominated by broad political narratives, Iqbalunnisa Hussain’s Purdah and Polygamy (1944) turns inward, using the Zenana as a microcosm to expose the pervasive network of patriarchy. This paper argues that Hussain’s work is a radical act of resistance precisely through its a-political focus, challenging the patriarchal matrix that male authors often reinforced. By unveiling the "purdah" on the female world, Hussain demonstrates how women exercise agency within severe constraints and ensures that the "doubly colonized" are not forgotten. Hussain’s zoomed-in lens on Zenana focuses on the intersection of gender, class, and religion to challenge them. Recuperating her voice is thus fundamental to challenging the political, male-centered narratives of the Partition-era India.